A price theory of altruistic identity - Kevin C. Corinth (American Enterprise Institute (AEI), 2016)
The key simplifying assumption is that individuals care about how generous they are conditional on being solicited, so that the number of times a person is solicited is the price of expressing a given level of altruistic identity. There are two main results. First, restricting entry among solicitors of altruistic acts increases the welfare of individuals who are solicited and increases aggregate giving net of solicitation costs. Second, collusion among solicitors is a Pareto improvement over competition even when entry is unrestricted. Thus, in markets where individuals are motivated by altruistic identity, policies that restrict entry may be helpful, and policies that restrict collusion may be harmful.
Keywords: A; 330; altruism